Material Relationship with Nias House Structural System in Response to Earthquake - Felicia Fantri; Ruth Aureline Marsha Buwono; Tiffany Aurelia Ongkojoyo; Josefira Jedine Santoso; Agus Dwi Hariyanto (Architectural Research Journal, 2022)
Nias Island is located on plates that collide with each other so it is very vulnerable to earthquakes. This is what makes the Nias community built so that they can adapt to the environment by utilizing wood materials in the structural system of the house. This study aims to determine the pattern of loading on Nias houses, as well as the placement of wood types in the composition of the structural elements of the house. This is to answer the formulation of the research problem, namely how is the relationship between the material and the structural system of the house to respond to the earthquake problem. The research was conducted by collecting data from journals and other sources, and making models from the data obtained. Then the data obtained were analyzed quantitatively by comparing the specifications of the wood to its placement in the structure of the house. The placement of the type of wood on the Nias house structure depends on the strength and durability of the wood, the higher the grade of wood, the wood is used as the main structure of the house and in the foundation of the house.